DECREASING SATISFACTION OF URBAN TRANSPORT PASSANGERS - Faizal Haris Eko Prabowo; Dwi Laela Rachmawulan; Nuryanti Taufik (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
Transportation services become one of the most needed facilities by many people. in every business activity, satisfaction becomes one of the factors to develop business in the transportation services industry. The decrease of passenger quantity and passenger satisfaction level at public transport service in Ciamis regency become some business problems. The purpose of this research to find out the level of passenger satisfaction and any factors that can affect passenger satisfaction in the district ciamis This research using survey methods. Survey in this research is to describe the phenomenon-related passenger satisfaction level and factors that affect passenger satisfaction in Ciamis. The study findings that there are three variable which affect passenger satisfaction such as service quality, price fairness and innovation also the level of passenger satisfaction was bad. Required participation from both business owner, driver and government to improve public transportation service system like improving service quality skills for driver, make a price fairness for whole passenger, and make some business innovation both method and business practice.